Towards a platform ecology: rethinking organisational models in the age of hyper-digitalisation - Amal SALLAKI; Youssef NAIT BELAID (International Journal of Scientific Research and Innovative Studies, 2026)
Hyper-digitalisation is profoundly transforming contemporary organisational models by redefining governance structures, value creation mechanisms and the dynamics of interaction between economic and institutional actors. Driven by the rise of technologies such as artificial intelligence, cloud computing, the Internet of Things and big data analytics, this transformation goes beyond the mere digitisation of processes to establish an organisational environment characterised by the constant interconnection of systems, data and actors. In this context, organisations operate in an environment marked by volatility, uncertainty, complexity and ambiguity, often described in the literature as VUCA. At the heart of this transformation lie digital platforms, which can no longer be viewed as mere technical infrastructures facilitating transactions. They now constitute genuine socio-technical ecosystems within which users, developers, partner companies, technological infrastructures and regulatory frameworks interact. Recent literature on digital ecosystems highlights that these platforms operate according to principles similar to those of natural ecosystems, where value emerges from the dynamic interaction between different interdependent actors (Parker, Van Alstyne & Choudary, 2016; Adner, 2017). From this perspective, the ecological metaphor allows us to understand platforms as complex adaptive systems, comparable to digital biomes hosting a diversity of interconnected actors and services. This ecological analogy refers to the emerging concept of ‘platform ecology’, which draws on these elements, amplified by network effects and the intensive flow of data. However, the rise of digital platforms is also accompanied by new forms of power asymmetry. The major global technology platforms – often referred to by the acronym GAFAM – concentrate a significant share of data governance and capture a large proportion of the value generated by interactions within their ecosystems. Research on ‘platform capitalism’ thus shows that platform operators can capture between 80% and 90% of the value produced by network effects, marginalising peripheral actors and reinforcing organisational dependencies (Srnicek, 2017; Zuboff, 2019). This concentration of digital power raises major issues regarding technological sovereignty, economic regulation and data governance. Furthermore, hyper-digitalisation also generates significant environmental externalities. The rapid growth of digital infrastructure – notably data centres and telecommunications networks – contributes to the increasing carbon footprint of the digital sector, which now accounts for a growing share of global greenhouse gas emissions. Estimates suggest that information and communication technologies could account for between 2% and 4% of global CO₂ emissions, with an upward trend linked to the expansion of digital services and data storage. These developments highlight the need to integrate the principles of digital frugality and environmental sustainability into the governance of digital platforms. In this context, the central research question can be formulated as follows: how can traditional organisational models, often characterised by hierarchical and siloed structures, be rethought in order to adapt them to a hyper-digitalised environment dominated by digital platforms? The aim of this article is to propose a conceptual framework based on ‘platform ecology’ in order to better understand the organisational dynamics at work in contemporary digital ecosystems and to identify the conditions for the emergence of more resilient, collaborative and sustainable organisational models. To address this issue, the study adopts a qualitative and interdisciplinary approach based on an in-depth literature review covering theories of digital platforms, the digital transformation of organisations, and systems ecology. This analysis is complemented by an examination of several illustrative cases drawn from the platform economy and digitalised higher education. The aim is not to produce an exhaustive empirical validation, but to propose a conceptual framework capable of shedding light on contemporary organisational transformations. The results of this analysis highlight three fundamental principles underpinning a platform ecology. The first concerns the transition from hierarchical organisational structures to holarchical and modular architectures that promote team autonomy and decentralised innovation. The second relates to the establishment of adaptive forms of governance capable of regulating data use, ensuring algorithmic transparency and limiting technological dependencies. Finally, the third principle concerns the integration of a logic of regenerative sustainability, involving the reduction of the digital sector’s ecological footprint and the adoption of more responsible growth models. In the Moroccan context, marked by the acceleration of national digital transformation strategies and the gradual widespread adoption of educational platforms in higher education, this reflection is of strategic importance. The growing integration of artificial intelligence and digital learning environments in Moroccan universities raises fundamental questions regarding the governance of academic data, digital sovereignty and digital inclusion. Ultimately, platform ecology offers an analytical perspective that allows us to move beyond a strictly technological view of digital transformation and to understand organisations as adaptive systems evolving within a globalised digital biotope. This approach thus opens up new avenues for rethinking organisational governance in the age of hyper-digitalisation, by linking technological innovation, social responsibility and ecological sustainability. Keywords: Hyper-digitalisation; Platform Ecology; Educational Policies; Digital Transformation in Higher Education; Algorithmic Governance; Digital Sovereignty; Sustainable Digital Education. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/665